Green Development through Modern Policy Redesign in the Disruptive Era within the Framework of Futuristic Transformation - Djafar, Franky (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2025)
The rapid technological disruption and the growing urgency of environmental degradation have challenged governments to redesign their policies toward sustainability. In developing countries such as Indonesia, policy implementation for Green Development remains fragmented and often disconnected from institutional capacity and local realities. This study aims to analyze how modern policy redesign supports Green Development within the framework of futuristic transformation by integrating innovation, collaboration, and technology into local governance. Using a qualitative descriptive method, data were collected from literature reviews, policy documents, and semi-structured interviews with key stakeholders in Gorontalo Regency, including government agencies, community organizations, and environmental groups. The research adopted a thematic synthesis approach supported by triangulation and ethical validation to ensure analytical credibility. The findings indicate that the success of Green Development relies not merely on regulatory frameworks but on adaptive governance that emphasizes participatory collaboration, technological innovation, and community empowerment. The creation of Integrated Policy Task Forces (IPTF) and digital monitoring tools such as e-Monev and SP4N LAPOR has enhanced transparency, cross-sector coordination, and real-time policy evaluation. Furthermore, social adaptation through eco-literacy programs and citizen participation has strengthened the sustainability culture at the local level. This study concludes that futuristic transformation in governance requires systemic redesign, combining institutional learning, digital inclusion, and collaborative networks to achieve long-term ecological and social resilience. The Gorontalo experience demonstrates that Green Development can serve as both a strategy and a governance paradigm that redefines how the state, society, and technology co-evolve toward sustainable futures.